IOM-UNHCR FRAMEWORK DOCUMENT − DEVELOPING STANDARD OPERATING PROCEDURES TO FACILITATE THE PROTECTION OF TRAFFICKED PERSONS - Stojanović, Bojan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
U junu 2020. godine, Međunarodna organizacija za migracije (International Organization for Migration) i Visoki komesar Ujedinjenih nacija za izbeglice (United Nations High Commissioner for Refugees) objavili su zajednički dokument kojim se razvijaju standardne operativne procedure (standard operating procedures) u cilju otkrivanja i zaštite žrtava trgovine ljudima. Reč je o Okvirnom dokumentu o razvoju standardnih operativnih procedura za olakšavanje identifikacije i zaštite žrtava trgovine ljudima (Okvirni dokument). Ovaj dokument predstavlja noveliranu i unapređenu verziju istovetnog dokumenta objavljenog decembra 2009. godine. Značaj Okvirnog dokumenta se ogleda u tome što će poslužiti ranoj i pravovremenoj identifikaciji žrtava trgovine ljudima i njihovom adekvatnom zbrinjavanju. Okvirni dokument dolazi u periodu kada je IOM postao povezana organizacija UN, te je došlo do približavanja u radu sa UN, a posebno sa UNHCR-om. U narednom periodu ostaje da se sagleda praktični značaj Okvirnog dokumenta i spremnost onih koji se susreću sa žrtvama trgovine ljudima da se služe ovim dokumentom. Прикажи више 1093/5000 In June 2020, the International Organization for Migration and the United Nations High Commissioner for Refugees published a joint document developing standard operating procedures to detect and protection of victims of trafficking. It is a Framework Document on the development of standard operating procedures to facilitate the identification and protection of victims of trafficking (Framework Document). This document is an amended and improved version of the same document published in December 2009. The importance of the Framework Document is reflected in the fact that it will serve for early and timely identification of victims of trafficking in human beings and their adequate care. The Framework Document comes at a time when the IOM has become an affiliated UN organization, and there has been a rapprochement in working with the UN, and in particular with the UNHCR. In the coming period, the practical significance of the Framework Document and the readiness of those who meet victims of trafficking in human beings to use this document remain to be considered.